Integrating Social Constructivism and Personal Construct Psychology Approaches: A Discourse Perspective - Fella Yorlanda (REiLA : Journal of Research and Innovation in Language, 2019)
This paper outlines the key features of discourse and psychological construct Psychology (PCP) in the past decades. This library research constructs its 59 related studies have been downloaded from the Google Scholar databases. The analysis in this study sees the crossroads between social constructivism and personal construct psychology (PCP) are increasingly being employs during the past decades. This convention is not only appropriate but seems to need each other. When construction sees cognition not as a person by any means leading to "behind" behaviour, but the configuration of the mind and sense that occur in action, the social context of the act that arises as an interest. At the same time, how cultural ideas or practices or "discourses" manifested in individuals and their actions, is very important. Therefore this study jump into conclusions that the discourse of psychology offers an opportunity to develop a coherent mix of social constituent ideas around the discourse, with PCP